The mediating role of self-care capacity in the relationship between perceived burden and quality of life among patients following mechanical valve replacement: a structural equation modeling analysis - Yuanyuan Yang; Xiaotian Zhang; Yunqing Chen; Yina Zhao; Shuizhen Ou; Wenhui Li; Yingshan Zhou (Frontiers in Cardiovascular Medicine, 2026)
Background Patients undergoing mechanical valve replacement face lifelong physical and psychological challenges that affect quality of life (QoL). While self-perceived burden and self-care capacity are both associated with QoL, the mediating mechanism by which self-perceived burden influences QoL through self-care capacity remains incompletely understood—particularly among patients with mechanical valve replacement. Clarifying this pathway could inform targeted nursing interventions for this population. Aim To examine the mediating role of self-care capacity in the relationship between self-perceived burden and QoL among patients with mechanical valve replacement, using structural equation modeling to evaluate both direct and indirect effects. Methods A cross-sectional design was used with 464 patients from a tertiary hospital in China. Participants completed validated questionnaires: the Self-Perceived Burden Scale(SPBS), the Exercise of Self-Care Agency Scale(ESCAS), and the 36-Item Short Form Survey(SF−36). Self-care capacity was modeled as a mediator within the structural equation modeling framework. Bootstrapping with 5,000 resamples was used to verify the significance of the indirect effect. Results Self-perceived burden was negatively correlated with both self-care capacity( r = −0.760, P < 0.001) and QoL( r = −0.826, P < 0.001). Self-care capacity partially mediated the association between self-perceived burden and QoL (indirect effect: β = −0.165, 95% bootstrap CI : −0.183 to −0.147, P < 0.001). The final model demonstrated good fit( χ 2 /df = 2.742, CFI = 0.969, RMSEA = 0.075). Conclusion Self-care capacity partially mediates the association between self-perceived burden and QoL in patients undergoing mechanical valve replacement. These findings suggest that interventions targeting both burden reduction and self-care enhancement may help improve QoL, though longitudinal and experimental research is needed to establish causal pathways and confirm clinical implications.